Polyelectrolyte Nanoparticles of Amphiphilic Chitosan/Pectin from Banana Peel as Potential Carrier System of Hydrophobic Molecules - Méndez, Paula A. (Polymers (Basel), 2020)
In this study, pectins were extracted from banana wastes Musa paradisiaca under different acidic conditions, obtaining pectins with different degrees of esterification (DE) depending on the acid type and pH. The formation of the polyelectrolyte nanoparticles was evaluated according to the DE of the pectin, the mass ratio of the polymers of pectin to amphiphilic chitosan (AmCh), and their concentration. The properties of the polyelectrolyte nanoparticles were evaluated at different pH and temperatures. The pectin with 24.3% DE formed polyelectrolyte nanoparticles through the electrostatic interaction with AmCh, which was evidenced by changes in the zeta potential and particle size. The study of mass ratio AmCh:Pectin, to get a stable system, showed that it must be at least equal (1:1), or AmCh must be in higher proportion (6:1, 50:1, 100:1), and the polymers concentration must be 1 mg/mL. The study of the temperature effect showed that, when the temperature increases, the particle size decreases, and the pH study showed a stable particle size for the polyelectrolyte nanoparticles in the range of pH 5–6. Nile Red (NR), a hydrophobic molecule, was encapsulated in the polyelectrolyte nanoparticles with a loading capacity of 1.8% and an encapsulation efficiency of 80%.